Differential Vascular Pathophysiologic Types of Intracranial Atherosclerotic Stroke: A High-Resolution Wall Magnetic Resonance Imaging Study. Issue 10 (October 2015) - Ryoo, Sookyung; Lee, Mi Ji; Cha, Jihoon; Jeon, Pyoung; Bang, Oh Young
Abstract : Background and Purpose—: Intracranial atherosclerotic stroke (ICAS) has various stroke mechanisms, including branch occlusive disease (BOD), subcortical infarcts caused by parent arterial disease occluding the perforator's orifice, and non-BOD, infarcts beyond the subcortical area caused by artery-to-artery embolism. To test whether these 2 types of ICAS had different vascular pathophysiologies, we compared the high-resolution magnetic resonance imaging characteristics between BOD and non-BOD ICAS. Methods—: Eighty patients with acute infarcts caused by ICAS of proximal middle cerebral artery or basilar artery without carotid/cardiac embolic sources or nonatherosclerotic causes were enrolled (36 BOD and 44 non-BOD patients). The steno-occlusive intracranial artery at the maximal stenosis was analyzed for vascular remodeling and wall enhancement. Results—: BOD had distinct radiological features in terms of vascular morphology and enhancement. BOD showed a milder stenosis than non-BOD ( P <0.001). Positive remodeling was more frequently observed in non-BOD than in BOD ( P =0.005). Wall area index was also lower in BOD. Plaque enhancement was observed in all but one non-BOD patient and in one fourth of BOD patients ( P =0.003). Although both types showed an eccentric enhancement, this enhancement was more frequently distributed in the BOD group on the side where the perforators arose. As the number of asymptomatic intracranial stenosis increased, the degree of stenosis (rho=0.513, P =0.003) increased in the BOD group, whereas enhanced plaque area (rho=0.343, P =0.030) increased in the non-BOD group. Conclusions—: Our data indicate that BOD is a common and unique form of ICAS, distinct from non-BOD. These 2 types of ICAS have different vascular pathophysiologies in terms of vascular remodeling and plaque characteristics. Abstract : Supplemental Digital Content is available in the text.